Pengaruh Teknik Relaksasi Nafas Dalam terhadap Penurunan Nyeri Post Sectio Caesarea - Arfan, Farmin; Darmiati, Darmiati; Ervi Santi, Tri (Yayasan Mandar Indonesia, 2024)
Birth can be done in two ways: normal or spontaneous delivery (born through the vagina) and abnormal delivery or delivery with the help of a procedure such as Caesarea Sectio (SC). In the process of cesarean section, surgery is performed, including cuts in the abdomen of the mother (laparatomy) and the uterus (histerectomy) to remove the baby. The study aims to identify nursing orphanages and pain disorders in patients with post-caesarean sections with therapeutic breathing relaxation techniques. This research uses a type of qualitative research with a case study approach on a single subject in the Sakura Room of RSUD H. Andi Depu. The results of this study obtained major and minor data at the time of post-operative examination patients complained of pain, shivering, restlessness, difficulty sleeping, and protective behavior. With the data of the study can be formulated nursing diagnosis with discomfort pain. The evaluation was obtained after being given nursing care for 3x24 hours, nursing problems with pain and comfort disorders were resolved. The conclusion is that providing breath relaxation therapy can reduce the pain scale of post-cesarean section patients.